2022
DOI: 10.1002/cpt.2624
|View full text |Cite
|
Sign up to set email alerts
|

Contextualized Drug–Drug Interaction Management Improves Clinical Utility Compared With Basic Drug–Drug Interaction Management in Hospitalized Patients

Abstract: Drug-drug interactions (DDIs) frequently trigger adverse drug events or reduced efficacy. Most DDI alerts, however, are overridden because of irrelevance for the specific patient. Basic DDI clinical decision support (CDS) systems offer limited possibilities for decreasing the number of irrelevant DDI alerts without missing relevant ones. Computerized decision tree rules were designed to context-dependently suppress irrelevant DDI alerts. A crossover study was performed to compare the clinical utility of contex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 49 publications
0
8
0
Order By: Relevance
“…28 However, since both drug (groups) have nephrotoxic potential and use of diuretics has been identified as a risk-factor for aminoglycosideinduced nephrotoxicity, caution is advisable when they are administered at the same time. [45][46][47] The PPV findings for our DDI-AKI and DDI-INR + e-triggers are encouraging. Use of e-triggers can largely automate the process of ADE detection, and save substantial time for patient chart review by clinical experts.…”
Section: Implications For Practice and Future Researchmentioning
confidence: 68%
See 3 more Smart Citations
“…28 However, since both drug (groups) have nephrotoxic potential and use of diuretics has been identified as a risk-factor for aminoglycosideinduced nephrotoxicity, caution is advisable when they are administered at the same time. [45][46][47] The PPV findings for our DDI-AKI and DDI-INR + e-triggers are encouraging. Use of e-triggers can largely automate the process of ADE detection, and save substantial time for patient chart review by clinical experts.…”
Section: Implications For Practice and Future Researchmentioning
confidence: 68%
“…This urges further improvement of the logic-based rules behind pDDI alerts to make them fit better to a specific clinical context and/or patient factors. 6,46,47 Given the high variety of pDDIs in the ICU, This study also underlines the multifactorial nature of adverse (drug) events in ICU patients. 48 This multifactorial nature explains why only a small proportion of DDI-ADEs in our study (6%) was assessed as having a nearly certain causality.…”
Section: Implications For Practice and Future Researchmentioning
confidence: 73%
See 2 more Smart Citations
“…For example, metamizole (dipyrone) generates theoretical DDIs that affect blood pressure and kidney functions due to being listed among other NSAIDs. Recently Wasylewicz et al have shown that contextualized DDI management can considerably decrease the number of irrelevant DDI alerts and thereby increase the time available to interpret relevant DDI alerts ( Wasylewicz et al, 2022 ). Although it may be difficult to operationalize certain factors to reduce unnecessary alerts, these factors can provide useful information for clinicians to decide whether to override an alert ( Reese et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%